P1446DIFFUSE IDIOPATHIC SKELETAL HYPEROSTOSIS IN PATIENTS UNDERGOING MAINTENANCE HEMODIALYSIS. (6th June 2020) - Ubukata, Masamitsu; Hara, Masaki; Suzuki, Hiroki; Asao, Rin; Nakamura, Yuya; Nakamura, Masayuki; Nitta, Kosaku; Ohsawa, Isao; Goto, Yoshikazu; Gotoh, Hiromichi
Abstract: Background and Aims: Diffuse idiopathic skeletal hyperostosis (DISH) is an idiopathic degenerative disease characterized by ossification of spinal ligaments and entheses, especially in the anterior longitudinal ligament. The ankylosed spine is prone to fracture with minor trauma and may result in spinal cord injury. It is usually asymptomatic and often diagnosed incidentally by computed tomography or other imaging methods. Several reports have revealed DISH as a risk factor for stroke, cardiovascular disease, and metabolic disorders, such as diabetes mellitus, hyperinsulinemia, obesity, dyslipidemia, and hyperuricemia. However, there are few reports of DISH in patients with end stage kidney disease (ESKD) requiring hemodialysis. Epidemiology, etiology and risk factors of DISH in patients with ESKD are unknown. We aimed to examine the prevalence and predictors of DISH in maintenance hemodialysis patients. Method: This was a case-control study using patients who received maintenance hemodialysis in our hospital in December 2018. The prevalence of DISH at enrollment was evaluated according to Resnick and Niwayama criteria by computed tomography (CT). The criteria is defined as follows: (1) Flowing ossification along the anterolateral aspect of at least four contiguous vertebral bodies, (2) Relative preservation of intervertebral disc height in the involved segment, (3) Absence of apophyseal joint bony ankylosis and sacroiliac joint erosion. We excluded patients who could not receive chest CT or with a history of thoracic spine surgery. Fisher exact tests were used to evaluate the relationships between categorical variables, and Kruskal-Wallis or Mann-Whitney U tests were used to evaluate continuous variables. We performed logistic regression analyses to identify variables that had a statistically significant association with DISH, as measured by the estimated odds ratio (OR) with the 95% confidence interval (CI). Results: A total of 395 consecutive patients were treated with maintenance hemodialysis in our hospital in December 2018. After excluding 4 patients who could not receive chest CT and 2 patients with a history of thoracic spine surgery, the remaining 389 patients were analyzed. The median age was 70 years, and 61.2% of patients were men. One hundred and twenty-three (31.6%) patients were diagnosed with DISH. We assigned them to the DISH group and other 266 patients to the control group. The patients with DISH were significantly more likely to have advanced age, male sex, high body weight, high bone mineral density, prior vertebral fracture, and diabetic nephropathy. Multivariate analysis showed that having DISH was significantly associated with advanced age (OR 1.06, 95%CI 1.03-1.09, P<0.001), high bone mineral density (OR1.02, 95%CI 1.00-1.03, P=0.03), prior vertebral fracture (OR3.22, 95%CI 1.23-8.41, P=0.017), diabetic nephropathy (OR 2.00, 1.03-3.90, P=0.041). Conclusion: The prevalence of DISH in maintenance hemodialysis patients was high. Advanced age, male sex, high body weight, high bone mineral density, prior vertebral fracture, and diabetic nephropathy were identified as a risk factor for DISH. Physicians involved in hemodialysis treatment should be aware of the existence of DISH as one of the comorbidities in the elderly ESKD patients.